On the roles of different foreign currencies in European bank lending - Signe Krogstrup; Cedric Tille (Graduate Institute of International and Development Studies, 2015)
We draw on a new data set on the use of Swiss francs and other currencies by European banks to assess the patterns of foreign currency bank lending. We show that the patterns differ sharply across foreign currencies. The Swiss franc is used predominantly for lending to residents, especially households. It is sensitive to the interest rate differential, exchange rate developments, funding availability, and to some extent international trade. Lending in other currencies is more used in lending to resident nonfinancial firms, and mostly in cross-border lending, where it is sensitive to funding costs and trade. Policy measures aimed at foreign currency lending have a clear impact on lending to residents. Our analysis shows that not all foreign currencies are alike, and that any policy aimed at the use of foreign currencies needs to take this heterogeneity into account.
Keywords: F32; F34; F36; 330; Swiss franc lending; foreign currency lending; cross-border transmission of shocks; European bank balance sheets